Evaluation of Interface and Cohesion Shear Strength of Mechanical Lap-Joint Between HTS Coated Conductors Intended for Segmented HTS Magnet. (17th November 2017) - Aparicio F., Luis E.; Ito, Satoshi; Hashizume, Hidetoshi
Abstract: This study evaluates the mechanical strength, failure mechanism and change in electrical resistance under shear stress of a mechanical lap joint of Rare-Earth Barium Copper Oxide high-temperature superconducting (HTS) tapes using indium as bonding material, which has been proposed for "remountable" (demountable) or segmented HTS magnet in future fusion reactors. Results from tensile shear tests using reinforced REBCO tapes along with an analysis on the failure mode demonstrated that contact conductivity is the critical parameter that defines joint's shear strength rather than joint pressure. Additionally, it was concluded that change in joint resistance when failure occur is not abrupt and its behavior as joint displaces depends on the failure mode of the joint.